2006
DOI: 10.1038/nsmb1087
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of single chromatin fibers revealed by torsional manipulation

Abstract: Magnetic tweezers are used to study the mechanical response under torsion of single nucleosome arrays reconstituted on tandem repeats of 5S positioning sequences. Regular arrays are extremely resilient and can reversibly accommodate a large amount of supercoiling without much change in length. This behavior is quantitatively described by a molecular model of the chromatin 3-D architecture. In this model, we assume the existence of a dynamic equilibrium between three conformations of the nucleosome, which are d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
201
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(226 citation statements)
references
References 44 publications
25
201
0
Order By: Relevance
“…They play essential roles in regulating the cellular level of supercoiling and the accessibility of DNA. In particular, the inherent dynamic behavior of nucleosome reorganization observed at the single-molecule level (Bancaud et al 2006) suggests that nucleosome dynamics respond to changes in supercoiling and, more specifically, to DNA torsion, which regulates binding of numerous proteins and controls cellular processes, including transcription and replication.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…They play essential roles in regulating the cellular level of supercoiling and the accessibility of DNA. In particular, the inherent dynamic behavior of nucleosome reorganization observed at the single-molecule level (Bancaud et al 2006) suggests that nucleosome dynamics respond to changes in supercoiling and, more specifically, to DNA torsion, which regulates binding of numerous proteins and controls cellular processes, including transcription and replication.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…Recent magnetic tweezers studies evaluated the response of a single chromatin fiber to applied torsion (Bancaud et al, 2006 and2007). The authors showed that nucleosomal arrays can absorb a significant amount of positive stress, without major changes to fiber length.…”
Section: Nucleosome Dynamics In Response To Torsional Stressmentioning
confidence: 99%
“…A complementary approach is to study individual chromatin fibers by using micromanipulation (Cui and Bustamante, 2000;Ladoux et al, 2000;Bennink et al, 2001;Brower-Toland et al, 2002;Leuba et al, 2003;Claudet et al, 2005;Gemmen et al, 2005;Bancaud et al, 2006). A major objective of such experiments has been the study of mechanically triggered changes in protein-DNA contacts, with an emphasis on force-driven opening of nucleosomes.…”
Section: Introductionmentioning
confidence: 99%